2010
DOI: 10.1530/eje-10-0710
|View full text |Cite
|
Sign up to set email alerts
|

Associations between cardiovascular risk, insulin resistance, β-cell function and thyroid dysfunction: a cross-sectional study in She ethnic minority group of Fujian Province in China

Abstract: Objective: To investigate the associations between cardiovascular risk, insulin resistance (IR), b-cell function and thyroid dysfunction in She ethnic minority group in China. Methods: We enrolled 5080 participants of She ethnicity in this analysis eventually. We measured serum TSH and thyroid peroxidase antibody (TPOAb) concentrations, blood glucose and insulin levels in both fasting and 2-h postprandial states, serum lipid levels, blood pressure (BP), brachial-ankle pulse wave velocity (baPWV), electrophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 42 publications
5
35
0
2
Order By: Relevance
“…The results from previous studies investigating the association of mild thyroid failure with insulin resistance, MS, and CHD are conflicting. SCH subjects have been shown to have similar (13), higher (7,8), or lower (12) insulin and HOMA-IR levels, compared with euthyroid control subjects. Similarly, Garduño-Garcia et al (13) found that the prevalence of MS was not different between SCH subjects and individuals with normal thyroid function, while another study demonstrated that the syndrome was significantly more prevalent in subjects with both overt thyroid failure and SCH than in euthyroid subjects (9).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…The results from previous studies investigating the association of mild thyroid failure with insulin resistance, MS, and CHD are conflicting. SCH subjects have been shown to have similar (13), higher (7,8), or lower (12) insulin and HOMA-IR levels, compared with euthyroid control subjects. Similarly, Garduño-Garcia et al (13) found that the prevalence of MS was not different between SCH subjects and individuals with normal thyroid function, while another study demonstrated that the syndrome was significantly more prevalent in subjects with both overt thyroid failure and SCH than in euthyroid subjects (9).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Although some studies have reported associations of SCH with insulin resistance (7,8), metabolic syndrome (MS) (7,9), and CHD (10,11), not all previous findings have been consistent (12,13,14). Recent studies in adults (9,15,16) and children (7) have shown that SCH is closely associated with NAFLD independent of potential confounders.…”
mentioning
confidence: 99%
“…Hypothyroidism is also associated with hyperinsulinaemia [13]. The slowed metabolic state of hypothyroidism not only slows the rate of glucose absorption from the gastro intestinal tract, but it also reduces the glucose utilization because of the insulin resistance [13,14]. In the current study, the significantly higher FPG of this group in comparison with that of the reference group, pointed to the possibility that hyperinsulinaemia and insulin resistance may be causing small excursions in the glucose levels in the prandial and the post prandial states.…”
Section: Resultsmentioning
confidence: 99%
“…[3] [4] But in diabetics patients, the prevalence is still greater and varies from 10 to 24% [4] [5] .These differences can be explained by different diagnostic criteria of thyroid dysfunction, degree of iodine intake in different people and different sensitivities of TSH and the large population diversity [6] .Thyroid diseases is a pathological state that adversely affect diabetics control and is commonly found in form of DM(diabetes mellitus) which is associated with advanced age in Type2 diabetes and autoimmune diseases in Type1 diabetes.DM appears to influence thyroid function in two sites ;firstly at the level of hypothalamic control of TSH release and secondly at the conversion of to in the peripheral tissue. The WHO estimate of diabetes prevalence for all age group worldwide was 2.8% in 2000 to 366 million in 2030 [7] .…”
Section: Introductionmentioning
confidence: 99%